1980
DOI: 10.1073/pnas.77.3.1627
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody to centromere (kinetochore) in scleroderma sera.

Abstract: Sera from patients with scleroderma contained several autoantibodies to nuclear antigens which were distinguished by different patterns of nuclear immunofluorescence staining. One of these autoantibodies reacted with centromeric regions of chromosomes. In chromosome spreads, the staining appeared as two small spheres at the centromere, resembling kinetochores. The antigenic determinant appeared to be a protein or polypeptide tightly bound to DNA. The autoantibody was reactive with centromeres of cells derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
296
2
8

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 666 publications
(314 citation statements)
references
References 19 publications
8
296
2
8
Order By: Relevance
“…Specific expression of HBx protein in ChangX and SNU368 cells but not in Huh7 and Chang cells were shown (Figure 2c). We first confirmed that BubR1 in SNU368 cells co-localized at the kinetochores of the condensed chromosomes with the kinetochore-specific marker, CREST (Moroi et al, 1980; data not shown). Notably, a portion of the HBx protein co-localized with hBubR1 at the kinetochores in SNU368 cells as well as in ChangX cells (Figure 2a …”
Section: Hbx Targets Hbubr1mentioning
confidence: 56%
“…Specific expression of HBx protein in ChangX and SNU368 cells but not in Huh7 and Chang cells were shown (Figure 2c). We first confirmed that BubR1 in SNU368 cells co-localized at the kinetochores of the condensed chromosomes with the kinetochore-specific marker, CREST (Moroi et al, 1980; data not shown). Notably, a portion of the HBx protein co-localized with hBubR1 at the kinetochores in SNU368 cells as well as in ChangX cells (Figure 2a …”
Section: Hbx Targets Hbubr1mentioning
confidence: 56%
“…The ACA patients were older at the onset of their first symptom attributable to PSS: mean age 44. 4 versus 39.2 years (P < 0.01). As expected from this age difference, 50% of the women with ACA were postmenopausal at the onset of their symptoms compared with only 26% of the women without ACA.…”
Section: Ofmentioning
confidence: 87%
“…In progressive systemic sclerosis, 3 types of antibodies appeared to be highly specific: antibody to Scl-70 antigen, antibody to centromere, and antinucleolar antibody (17,18). Antibodies to nRNP were also occasionally detected.…”
Section: Discussionmentioning
confidence: 99%